Assembly of DNA onto the histone octamer facilitates the B-to-Z transition. Issue 5 (May 1986) - Miller, F. D.; Rattner, J. B.; van de Sande, J. H.
Abstract : Nucleosomal core particles containing the right- and left-handed conformations of DNA were examined for their ability to support the B→Z or Z→B transition. Nucleosomes were assembled onto the B- and Z-conformations of poly[d(Gm5C)] and the B-conformation of poly[d(GC)] as previously described (1). Absorbance and circular dichroic spectroscopy indicated that the DNA on all three core particle populations could undergo the conformational B↔Z transition. Further, the right- to left-handed transition for both poly[d(Gm5C)] and poly[d(GC)] appeared to be facilitated by the DNAs association with the histone octamer. The DNA remained associated with the protein core subsequent to the transition, and electron microscopy and sedimentation velocity analysis indicated that there were no gross changes in nucleosomal structure. However, a change in the sedimentation value of the poly[d(Gm5C)] core particles was detected when the conformation of the DNA was altered from B to Z, resulting in a lower S20, w value for the Z-form particles than for the corresponding B-form particles.